2015
DOI: 10.1007/s10072-015-2124-2
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of ICHD-3 beta diagnostic criteria for Tolosa–Hunt syndrome: a study of 22 cases of Tolosa–Hunt syndrome

Abstract: The objective of the study was to evaluate the amended International Classification of Headache Disorders (third edition, beta version, ICHD-3 beta) with a retrospective analysis. A total of 22 patients diagnosed with painful ophthalmoplegia and Tolosa-Hunt syndrome (THS) in our hospital were retrospectively studied. The following clinical data were collected: symptoms, signs, location of inflammatory tissue, time interval of paresis following the onset of pain, pain and signs of resolution, follow-up and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 20 publications
5
51
1
1
Order By: Relevance
“…Studies suggested thin the slice thickness and enhanced MRI with fat suppression maybe another option. [12]An observation by applying high resolution MR sequences(slice thickness = 2.5-3 mm), from Schuknecht and his colleagues, displayed 75% pathologic nding. [13] Hao gave post-contrast fat suppression MRI scans to the "non-enhanced MRI negative" patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested thin the slice thickness and enhanced MRI with fat suppression maybe another option. [12]An observation by applying high resolution MR sequences(slice thickness = 2.5-3 mm), from Schuknecht and his colleagues, displayed 75% pathologic nding. [13] Hao gave post-contrast fat suppression MRI scans to the "non-enhanced MRI negative" patients.…”
Section: Discussionmentioning
confidence: 99%
“…THS can be treated with corticosteroids, with the disappearance of eye pain within a number of days (approximately 1 to 4 days) and alleviation of ophthalmoplegia within a number of weeks (7 to 60 weeks) from the start of treatment [5,8]. The patient in this case received intravenous methylprednisolone at 1000 mg/day for 3 days as steroid pulse therapy and then started receiving oral prednisolone at 60 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Although a straightforward dose-response effect on psychiatric adverse reactions has not yet been elucidated, these reports suggest that a prednisolone dose less than 40 mg/ day might safely prevent these reactions. Steroid therapy for THS currently lacks any protocol-specified dosage; accordingly, corticosteroid therapy involves varied doses, methods, and durations (Table 1) [2][3][4][5][6][7][8]. An initial prednisolone dose of 1.0 to 1.5 mg/kg/day is commonly found in available reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reported cases of Tolosa-Hunt syndrome had additional involvement of the fifth nerve (commonly the first division) or optic, seventh, or eighth nerve. Sympathetic innervation of the pupil is affected in about 30% of patients (20). Most cases are unilateral, but rarely are also bilateral.…”
Section: Symptomatologymentioning
confidence: 99%